Developing multicultural intergroup dialogue at a Japanese university: Toward sustainable and holistic international student support - Tokunaga, Tomoko; Sawata, Akira; Kawano, Yoshiyuki (Journal of International Students, 2026)
While Japanese universities have adopted intercultural collaborative learning (ICL) to promote holistic international student support, ICL often lacks a social justice framework necessary for sustainable and equitable practices. This study addresses this gap by integrating intergroup dialogue (IGD)—a social justice pedagogy—into ICL. It examines how international and domestic students raise awareness of diversity, equity, and sustainability issues by participating in multicultural IGD at a Japanese university. We co-developed a workshop with a company and conducted interviews. The findings revealed that IGDs empowered international students and affirmed their identities, increased domestic students’ critical consciousness, and improved advocacy attitudes while addressing challenges in institutional change.